Kelas Keuangan Desa: Pemberdayaan SDM Pemerintah Desa dan BUMDesma dalam Penyusunan Studi Kelayakan Usaha Desa di Kecamatan Bendosari Sukoharjo - Ahmad Dzakiyuddin; Made Wedaswari (Pusat Riset dan Inovasi Nasional, 2026)
This community service program aims to strengthen the capacity of village government and BUMDesma human resources in preparing business feasibility studies. The program was conducted in Bendosari District, Sukoharjo Regency, where village economic potential is relatively high but not optimally supported by data-based business planning. The method used is Participatory Learning and Action (PLA) combined with project-based learning through stages of socialization, training, technology implementation, mentoring, and evaluation. The results show a significant improvement in participants’ understanding of village potential mapping, financial projections, and feasibility analysis. Participants were able to produce village economic potential mapping documents, feasibility study reports, and financial templates. This program contributes to improving village business governance towards more transparent, accountable, and sustainable practices. Strengthening financial literacy and feasibility analysis is essential for ensuring sustainability of village enterprises.